Contribution of non-endothelium-dependent substances to exercise hyperaemia: are they O(2) dependent? - Marshall, Janice M (Blackwell Science Inc, 2012)
This review considers the contributions to exercise hyperaemia of substances released into the interstitial fluid, with emphasis on whether they are endothelium dependent or O(2) dependent. The early phase of exercise hyperaemia is attributable to K(+) released from contracting muscle fibres and acting extraluminally on arterioles. Hyperpolarization of vascular smooth muscle and endothelial cells induced by K(+) may also facilitate the maintained phase, for example by facilitating conduction of dilator signals upstream. ATP is released into the interstitium from muscle fibres, at least in part through cystic fibrosis transmembrane conductance regulator-associated channels, following the fall in intracellular H(+). ATP is metabolized by ectonucleotidases to adenosine, which dilates arterioles via A(2A) receptors, in a nitric oxide-independent manner. Evidence is presented that the rise in arterial [Image: see text] achieved by breathing 40% O(2) attenuates efflux of H(+) and lactate, thereby decreasing the contribution that adenosine makes to exercise hyperaemia; efflux of inorganic phosphate and its contribution may likewise be attenuated. Prostaglandins (PGs), PGE(2) and PGI(2), also accumulate in the interstitium during exercise, and breathing 40% O(2) abolished the contribution of PGs to exercise hyperaemia. This suggests that PGE(2) released from muscle fibres and PGI(2) released from capillaries and venular endothelium by a fall in their local [Image: see text] act extraluminally to dilate arterioles. Although modest hyperoxia attenuates exercise hyperaemia by improving O(2) supply, limiting the release of O(2)-dependent adenosine and PGs, higher O(2) concentrations may have adverse effects. Evidence is presented that breathing 100% O(2) limits exercise hyperaemia by generating O(2)(−), which inactivates nitric oxide and decreases PG synthesis.